Corporation of Bombay acronym in gold leaf - Ghosh, Ayan (2023)
The Corporation Hall is richly detailed with moulded wooden panels covered in gold leaf. Busts of figures representing the various communities of Mumbai hold heraldic shields with the initials CB marked on them (CB stands for Corporation of Bombay). The ceiling is made of unpolished teakwood.